KONTRIBUSI SOSIAL PERTUKARAN MAHASISWA MERDEKA 2 DI DESA KALISONGO, KABUPATEN MALANG, JAWA TIMUR - Alparizi, Lalu Rizki (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2024)
Merdeka 2 exchange students of State University of Malang carried out social contribution activities as one of a series of agendas in the Nusantara Module. The activity was carried out in Kalisongo village, Malang Regency, East Java. This activity involves youth to participate in socialization and content creation training in order to promote and introduce traditions in the local village. Through this activity, it is expected to provide new experiences and insights to students and youth where the social contribution is carried out.